Cost, risk, and avoidance of inbreeding in a cooperatively breeding bird - Leedale, Amy E; Simeoni, Michelle; Sharp, Stuart P; Green, Jonathan P; Slate, Jon; Lachlan, Robert F; Robinson, Elva J H; Hatchwell, Ben J (Proceedings of the National Academy of Sciences - PNAS, 2020)
Inbreeding is often avoided in natural populations by passive processes such as sex-biased dispersal. But, in many social animals, opposite-sexed adult relatives are spatially clustered, generating a risk of incest and hence selection for active inbreeding avoidance. Here we show that, in long-tailed tits ( ), a cooperative breeder that risks inbreeding by living alongside opposite-sex relatives, inbreeding carries fitness costs and is avoided by active kin discrimination during mate choice. First, we identified a positive association between heterozygosity and fitness, indicating that inbreeding is costly. We then compared relatedness within breeding pairs to that expected under multiple mate-choice models, finding that pair relatedness is consistent with avoidance of first-order kin as partners. Finally, we show that the similarity of vocal cues offers a plausible mechanism for discrimination against first-order kin during mate choice. Long-tailed tits are known to discriminate between the calls of close kin and nonkin, and they favor first-order kin in cooperative contexts, so we conclude that long-tailed tits use the same kin discrimination rule to avoid inbreeding as they do to direct help toward kin.